Road Traffic Safety Development Trends in Latvia - Juris Kreicbergs; Juris Smirnovs; Aldis Lama; Janis Smirnovs; Atis Zarins (The Baltic Journal of Road and Bridge Engineering)
The main focus of this article is on the road traffic safety development trends in Latvia. Soon after the regain of independence at the beginning of the 1990s, road traffic safety characteristics in Latvia were the worst in the Latvian history. The increase of car availability and affordability made the car a major road vehicle. The implementation of road safety programmes contributed to essential improvement of road traffic safety in Latvia. The number of road accident fatalities in 2020 compared to 1991 decreased more than sevenfold. Nevertheless, the current Latvian road traffic safety statistics is well below the average level of the EU member states and even the pandemics did not cause similar reduction as in most member states. This indicates that great improvement is still needed. The article shows the Latvian experience in road traffic safety enhancements and discusses the measures to improve road traffic safety.